Formulation Development of Meloxicam Binary Ethosomal Hydrogel for Topical Delivery: In Vitro and In Vivo Assessment - Ahdaq Ali Faisal Al-Ameri; Fatima Jalal Al-Gawhari (MDPI AG, 2024)
The article aimed to formulate an MLX binary ethosome hydrogel for topical delivery to escalate MLX solubility, facilitate dermal permeation, avoid systemic adverse events, and compare the permeation flux and efficacy with the classical type. MLX ethosomes were prepared using the hot method according to the Box-Behnken experimental design. The formulation was implemented according to 16 design formulas with four center points. Independent variables were (soya lecithin, ethanol, and propylene glycol concentrations) and dependent variables (vesicle size, dispersity index, encapsulation efficiency, and zeta potential). The design suggested the optimized formula (MLX-Ethos-OF) with the highest desirability to perform the best responses formulated and validated. It demonstrates a 169 nm vesicle size, 0.2 dispersity index, 83.1 EE%, and −42.76 mV good zeta potential. MLX-Ethos-OF shows an amorphous form in PXRD and a high in vitro drug release of >90% over 7 h by diffusion and erosion mechanism. MLX-Ethos-OF hyaluronic acid hydrogel was fabricated and assessed. It shows an elegant physical appearance, shear thinning system rheological behavior, good spreadability, and skin-applicable pH value. The ex vivo permeation profile shows a flux rate of 70.45 μg/cm2/h over 12 h. The in vivo anti-inflammatory effect was 53.2% ± 1.3 over 5 h. compared with a 10.42 flux rate and 43% inflammatory inhibition of the classical ethosomal type. The conclusion is that binary ethosome is highly efficient for MLX local delivery rather than classical type.